Quality of Animal Experiments in Anti-Angiogenic Cancer Drug Development – A Systematic Review - Martić-Kehl, Marianne Isabelle (PLoS One, 2015)
Translation from preclinical animal research to clinical bedside has proven to be difficult to impossible in many fields of research (e.g. acute stroke, ALS and HIV vaccination development) with oncology showing particularly low translation rates (5% vs. 20% for cardiovascular diseases). Several investigations on published preclinical animal research have revealed that apart from plain species differences, translational problems can arise from low study quality (e.g. study design) or non-representative experimental conditions (e.g. treatment schedule). This review assessed the published experimental circumstances and quality of anti-angiogenic cancer drug development in 232 in vivo studies. The quality of study design was often insufficient; at least the information published about the experiments was not satisfactory in most cases. There was no quality improvement over time, with the exception of conflict of interest statements. This increase presumably arose mainly because journal guidelines request such statements more often recently. Visual inspection of data and a cluster analysis confirmed a trend described in literature that low study quality tends to overestimate study outcome. It was also found that experimental outcome was more favorable when a potential drug was investigated as the main focus of a study, compared to drugs that were used as comparison interventions. We assume that this effect arises from the frequent neglect of blinding investigators towards treatment arms and refer to it as hypothesis bias. In conclusion, the reporting and presumably also the experimental performance of animal studies in drug development for oncology suffer from similar shortcomings as other fields of research (such as stroke or ALS). We consider it necessary to enforce experimental quality and reporting that corresponds to the level of clinical studies. It seems that only clear journal guidelines or guidelines from licensing authorities, where failure to fulfill prevents publication or experimental license, can help to improve this situation.